Contemporary Pornography and Sexual Socialization - Štulhofer, Aleksandar (2007)
Our presentation discusses the contemporary role of sexuality in sexual culture and sexual socialization. In spite of the fact that pornography is normalized and ubiquitous in the West today, there is a notable lack of rigorous research into possible effects of pornography on sexual socialization. This presentation offers a theoretical model of such influence and its preliminary empirical exploration. Being interested in sex-positive outcomes of sexual socialization, we focus on determinants of sexual satisfaction. As our findings suggest, pornography consumption may have both negative and positive effects on sexual satisfaction of young adults. Among men who participated in our large online study, the main effect of pornography on sexual satisfaction was negative and indirect. We found pornography use associated with lower levels of intimacy, which in turn had negative impact on sexual satisfaction. In conclusion, directions for further research are sketched.